The removal of iron from waterlogged archaeological wood: efficacy and effects on the room temperature wood properties. Issue 2 (4th March 2023) - Pecoraro, Elisa; Pelé-Meziani, Charlène; Macchioni, Nicola; Lemoine, Gwenaël; Guilminot, Elodie; Shen, Dawa; Pizzo, Benedetto
ABSTRACT: Present results provided new information on the practice of removing iron from waterlogged wood using chelating agents. Two series of samples were selected: small waterlogged wood samples of Quercus spp., Pinus sylvestris L. and Pinus pinaster Aiton, and a portion from the dismantled shipwreck Huguangjiao I. Iron extractions were carried out using disodium ethylenediaminetetraacetic acid (EDTA) and diethylenetriaminepentaacetic acid (DTPA). Samples were characterized by environmental scanning electron microscopy coupled with dispersive energy spectrometry, micro-Raman spectroscopy, atomic absorption spectroscopy, Fourier transform infrared spectroscopy and dynamic mechanical analysis (DMA), the latter used to evaluate viscoelastic properties. The extraction efficiency of both products was good, although it depended on the wood state of preservation, being higher in more decayed material. Still, the extraction procedures induced a limited effect on the decayed wood tissue, affecting both cell wall chemical composition and physical characteristics. Moreover, a significant difference existed between the two agents. In decayed hardwoods, they had an impact on both E' (decrease) and tanδ (increase), mostly apparent for DTPA. The difference between DTPA and EDTA was also more evident when the frequency was varied in DMA tests. In contrast, the well-preserved softwood was not affected by the considered treatments.